2016
DOI: 10.1364/ol.41.000436
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring of the Brillouin gain for on-chip widely tunable and reconfigurable broadband microwave photonic filters

Abstract: An unprecedented Brillouin gain of 44 dB in a photonic chip enables the realization of broadly tunable and reconfigurable integrated microwave photonic filters. More than a decade bandwidth reconfigurability from 30 up to 440 MHz, with a passband ripple <1.9  dB is achieved by tailoring the Brillouin pump. The filter central frequency is continuously tuned up to 30 GHz with no degradation of the passband response, which is a major improvement over electronic filters. Furthermore, we demonstrate pump tailoring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 125 publications
(74 citation statements)
references
References 26 publications
0
66
0
Order By: Relevance
“…2 RF tones were generated by an RF signal generator (Tabor, 400 MHz) separated by 20 MHz and were modulated onto the IM. The resultant broadened pump was used to increase the bandwidth of the SBS response and thus the filter 14, 39 . 23 ns pulses were generated from an RF signal Generator (Tabor, 1 GHz) and then up-converted from baseband by mixing with a 14.1 GHz RF tone using an RF mixer (Mini Circuits).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 RF tones were generated by an RF signal generator (Tabor, 400 MHz) separated by 20 MHz and were modulated onto the IM. The resultant broadened pump was used to increase the bandwidth of the SBS response and thus the filter 14, 39 . 23 ns pulses were generated from an RF signal Generator (Tabor, 1 GHz) and then up-converted from baseband by mixing with a 14.1 GHz RF tone using an RF mixer (Mini Circuits).…”
Section: Methodsmentioning
confidence: 99%
“…This has motivated the development of on-chip platforms 30, 31 for generating high SBS gains in silicon 3234 and chalcogenides 35, 36 for various microwave photonic functionalities 37–43 . Nevertheless, in each of these cases the spectral resolution was mainly governed by the material properties, with the increase in the bandwidth possible through a cascade of pumps spaced at different frequencies 39 . In contrast, the reduction in the bandwidth is challenging and could only be achieved by increasing the pump power, negatively affecting the power-efficiency of the device 40 .…”
Section: Introductionmentioning
confidence: 99%
“…On-chip stimulated Brillouin scattering (SBS) is another nonlinear effect that has been explored for implementing RF filters. Utilizing the SBS effect in a 6.5-cm-long As2S3 waveguide, Morrison et al [109], Byrnes et al [110], and Choudhary et al [111] demonstrated respectively an RF bandstop filter and narrow bandpass filter with tunable bandwidth and center frequency as shown in Figure 26B. In a later work Marpaung et al [44], associated such SBS effect with a particular modulation spectrum comprising uneven sidebands and therewith demonstrated a highly selective RF notch filter with a very deep notch of 60 dB and a large frequency tuning range of 30 GHz as shown in Figure 27A.…”
Section: Various Filter Implementationsmentioning
confidence: 99%
“…This stimulated Brillouin scattering (SBS) approach is based on a single passband microwave photonic filter as described in Figure 9a [32]. The input RF signal is modulated onto an optical carrier using a phase modulator, such that two sidebands with a phase difference of π separated from the RF carrier frequency is resulted.…”
Section: Multiband Filter Based On Tailoring Of the Brillouin Gain Inmentioning
confidence: 99%